Effect of Comprehensive Cerebral Protection Program on Cerebral Oxygen Metabolism and Vascular Endothelial Function in Elderly Patients with Acute Cerebral Infarction - Meihong ZHOU; Zhaojun HUANG (Tehran University of Medical Sciences, 2019)
Background: We aimed to explore the effect of comprehensive cerebral protection on cerebral oxygen metabolism and vascular endothelial function in elderly patients with acute cerebral infarction. Methods: A total of 168 elderly patients with acute cerebral infarction treated in The First Affiliated Hospital of Nanchang University, China from January 2016 to January 2018 were selected. The patients were divided into a control group and an observation group using random number method, n=84. Patients in the observation group were given comprehensive cerebral protection treatment, and patients in the control group were treated with conventional standardized treatments. The changes of cerebral oxygen metabolism, hemorheology and vascular endothelial function before and after treatment were compared between the two groups. Results: After treatment, oxygen content in arteries and internal jugular veins (Da-vO2), ofoxygen uptake fraction (OEF), Oxygen saturation (SpO2), nitric oxide (NO) were increased in both groups in comparison to before treatment, jugular venous oxygen saturation (SjvO2), brain oxygen uptake rate (ERO2), endothelin (ET), intracranial pressure (ICP), whole blood viscosity, plasma viscosity, reduced viscosity of whole blood, and hematocrit were decreased. However, the changes in the observation group were larger than those in the control group, the difference was statistically significant (P<0.05). Conclusion: The treatment of cerebral infarction in elderly patients with acute cerebral infarction can effectively improve the cerebral oxygen metabolism and vascular endothelial function and improve the blood rheology, which has important clinical value.